PENGGUNAAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS ARGUMENTASI MAHASISWA - inggriyani, feby (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
The problem in this research is the low ability of students in writing arguments. Therefore, efforts are needed to resolve this problem. This research aims to determine the improvement in students' argumentative writing skills using the Problem Based Learning model. The research method uses Classroom Action Research in the form of qualitative descriptive with the data obtained in the form of test and non-test results in the form of observations and interviews. The subjects of this research were 29 students of the Primary School Teacher Education Study Program, semester 1 of the 2023/2024 academic year. Based on research data, it was found that there was an increase in the assessment of learning implementation and an increase in students' ability to write arguments in each cycle using the Problem Based Learning learning model.